Paradigmas de formação docente em cursos de licenciatura em química no estado do Acre na região da Amazônia Legal brasileira - Costa, Roger Vinicius Nunes Queiroz da (2023)
With regard to teacher training, the Supervised Internship (ES) and Practice as a Curriculum Component (PCC) have been themes of several studies and debates undertaken around the inadequacies, inexistence or little contribution in the preparation of teachers for the school reality. The dissociation between teaching and reality that is presented in the proposed ideological approaches are studies by different authors and projects that propose to analyze the most varied forms, which make up the theory and practice axis. This axis has an important meaning in teacher training, as it guides the concept of unit transformation, that is, the relational context between theory and practice that should not be divergent or juxtaposed, but integrated and related. The Supervised Internship constitutes one of the most important stages in the academic life of Degree students and, complying with the requirements of the Law of Guidelines and Bases of National Education - LDB (Law No. they can favor the relationship between theory and practice, the strengthening of the teaching identity and the preparation for praxis. Although the Resolution of the National Council of Education/Plenary Council (CNE/CP) nº. 1 and no. 2 of 2002, Resolution no. 2 of 2015, and Resolution CNE/CP no. 2 of 2019 determine the mandatory 400h of Supervised Internship and 400h of Curricular Component Practice, what is the understanding and the training paradigm (movements - theoretical, methodological and epistemological) present in the PPC analyzed (PPC 1 - IFAC; PPC 2 - UFAC)? In addition, we sought to identify, according to Diniz-Pereira (2014), which formative paradigm that Higher Education Institutions present in terms of the Supervised Internship and the Curricular Component Practice. In this perspective, this qualitative research assumes the Case Study method as a method, seeking to answer the following question: how is the mandatory Supervised Internship expressed, and Practice as a Curricular Component (PCC) in the Pedagogical Projects of Courses in Higher Education Institutions (HEI) public in the state of Acre? For the analysis of field texts, Textual Discursive Analysis (DTA) was used, which develops from the fragmentation of texts, unitarization, categorization and capture of the new emergent. In this way, the following categories emerged, a posteriori: i) conception of supervised internship; ii) theory and practice and teaching identity. In the research texts, it is shown that there is homogeneity in the Pedagogical Projects of the Course analyzed with regard to the conceptions of SE, the PCC in one of the HEIs is not defined, presenting an insufficient workload, not meeting the current educational public policies. It appears that the training paradigm is shifting towards practical rationality, centered on the model of teaching as a craft. It was also noted that there were few proposals that could, in fact, lead the intern to the praxis that can be done based on education through research.